2016
DOI: 10.1002/lom3.10122
|View full text |Cite
|
Sign up to set email alerts
|

First report of a novel multiplexer pumping system coupled to a water quality probe to collect high temporal frequency in situ water chemistry measurements at multiple sites

Abstract: The increasing availability and use of high-frequency water quality sensors has enabled unprecedented observations of temporal variability in water chemistry in aquatic ecosystems. However, we remain limited by the prohibitive costs of these probes to explore spatial variability in natural systems. To overcome this challenge, we have developed a novel auto-sampler system that sequentially pumps water from up to 12 different sites located within a 12 m radius to a single water quality probe. This system is able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
2
24
1
Order By: Relevance
“…The zero order, first order, and Monod models were chosen because they have been used to model NO 3 -N removal in wetlands in past experiments [25,36]. The efficiency loss model was chosen because to our knowledge it had not been explored prior to this study in wetlands, but has been observed to model NO 3 -N removal well in streams [37][38][39].…”
Section: No 3 -N Removal Kinetic Modelsmentioning
confidence: 99%
“…The zero order, first order, and Monod models were chosen because they have been used to model NO 3 -N removal in wetlands in past experiments [25,36]. The efficiency loss model was chosen because to our knowledge it had not been explored prior to this study in wetlands, but has been observed to model NO 3 -N removal well in streams [37][38][39].…”
Section: No 3 -N Removal Kinetic Modelsmentioning
confidence: 99%
“…The spectrophotometer and MPS measurement sequence was adjusted such that the stock tank and each column outflow concentrations were measured at 2‐h intervals. Nitrate concentrations were calculated from the measured absorbance following methods previously described (Birgand et al, 2016; Etheridge et al, 2014; Vaughan et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…, Birgand et al. ). Water clarity can also be observed from sensing technologies via aircraft and satellites, which greatly expand the geographic coverage of lakes that can be studied globally (Lee et al.…”
Section: Increasing Collaboration Between Computer Scientists and Ecomentioning
confidence: 99%
“…Now, new optical sensors developed by computer and electrical engineers provide highly sensitive measures of water quality every second, equating to over 30 million observations per year from one sensor and potentially billions of observations per year collected by multiple sensors on a single lake (Carey et al 2012, Weathers et al 2013. Consequently, the volume and variety of data on lake water clarity and other water spectral characteristics are growing exponentially, as these data are indicator metrics of water quality (Watras et al 2015, Birgand et al 2016. Water clarity can also be observed from sensing technologies via aircraft and satellites, which greatly expand the geographic coverage of lakes that can be studied globally (Lee et al 2018).…”
Section: Benefits To Ecologymentioning
confidence: 99%